1999
DOI: 10.1093/ajcn/70.6.1090
|View full text |Cite
|
Sign up to set email alerts
|

Receiver operating characteristic analysis of body mass index, triceps skinfold thickness, and arm girth for obesity screening in children and adolescents

Abstract: The results suggest that triceps skinfold thickness gives the best results for obesity screening in adolescents aged 10-15 y. BMI and upper arm girth were reasonable alternatives, except in 14-15-y-old boys, in whom both indexes were only marginally able to discriminate obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
158
1
35

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(208 citation statements)
references
References 22 publications
11
158
1
35
Order By: Relevance
“…Must et al (1991), too, have reported a similar observation using NHANES-I data. This is consistent with the greater gains in muscle and bone experienced by boys during adolescence and greater gains in body fat experienced by girls (Sardinha et al, 1999). Therefore, it cannot be denied that these variations in age, sex and maturation impose more limitations on BMI as a measure of adiposity in the pediatric population than in adult population (Neovius et al, 2004).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Must et al (1991), too, have reported a similar observation using NHANES-I data. This is consistent with the greater gains in muscle and bone experienced by boys during adolescence and greater gains in body fat experienced by girls (Sardinha et al, 1999). Therefore, it cannot be denied that these variations in age, sex and maturation impose more limitations on BMI as a measure of adiposity in the pediatric population than in adult population (Neovius et al, 2004).…”
Section: Discussionsupporting
confidence: 57%
“…Similar is the case with TSFT (12 vs 16.4 mm for boys; and 14 vs 22.3 mm for girls), indicating that most cutoffs appear much lower than the conventional ones. Recently, Sardinha et al (1999) too have reported that the recommended cutoffs for Portugese boys and girls also correspond to lower percentiles than those recommended for US boys and girls, whereas Malina and Katzmarzyk (1999) show cutoffs for body fat to be more sensitive than BMI. Our observations, therefore, indicate the need for validation of conventional cutoffs in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent BF% values for definition of excess body fat in female adolescents range between 30 and 35%. BF% cutoffs for excess body fat in males are 25 and 30% for adolescents aged 10-15 years and between 20 and 25% when subjects up to the age of 18 years are considered (Weststrate and Deurenberg, 1989;Sardinha et al, 1999;Taylor et al, 2002Taylor et al, , 2003. Morrison et al (2001) reported BF% values obtained with the same equations, in females aged 9-19 years; when compared with our girls, BF% values were higher in American children, except for white females at the age of 13 years.…”
Section: Discussionmentioning
confidence: 81%
“…However, future studies with a longitudinal design are needed to confirm our findings. 41 in their study with children and adolescents aged 10-15 years observed that BMI and triceps skinfold thickness accurately predicted obesity (AUCs ranged 44 . Differences between studies may be due to methodological differences in data collection or even in data preparation (i.e.…”
mentioning
confidence: 95%